2011
DOI: 10.1099/vir.0.028381-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection with human coronavirus NL63 enhances streptococcal adherence to epithelial cells

Abstract: Understanding the mechanisms of augmented bacterial pathogenicity in post-viral infections is the first step in the development of an effective therapy. This study assessed the effect of human coronavirus NL63 (HCoV-NL63) on the adherence of bacterial pathogens associated with respiratory tract illnesses. It was shown that HCoV-NL63 infection resulted in an increased adherence of Streptococcus pneumoniae to virus-infected cell lines and fully differentiated primary human airway epithelium cultures. The enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…Previously, we confirmed that HRSV infection upregulates expression of platelet-activating factor receptor (PAF-R), a receptor for S. pneumonia, on A549 (Yokota et al, 2010). Similar phenomena are observed during infection with rhinovirus and coronavirus, which upregulate expression of fibronectin, carcinoembryonic antigen-related cell adhesion molecule, and PAF-R on respiratory epithelial cells (Ishizuka et al, 2003;Golda et al, 2011). However, little is known about how PM attaches to virus-infected respiratory cells.…”
Section: Discussionsupporting
confidence: 67%
“…Previously, we confirmed that HRSV infection upregulates expression of platelet-activating factor receptor (PAF-R), a receptor for S. pneumonia, on A549 (Yokota et al, 2010). Similar phenomena are observed during infection with rhinovirus and coronavirus, which upregulate expression of fibronectin, carcinoembryonic antigen-related cell adhesion molecule, and PAF-R on respiratory epithelial cells (Ishizuka et al, 2003;Golda et al, 2011). However, little is known about how PM attaches to virus-infected respiratory cells.…”
Section: Discussionsupporting
confidence: 67%
“…To rule out such a possibility, a quantitative RT-PCR -based assay was employed to assess the HCoV-NL63 yield in the cell culture supernatant. The assay was performed as previously described (Golda et al, 2011) and the number of RNA copies per milliliter of cell culture supernatant was assessed. Conducted analysis clearly shows that in the presence of the studied polymers there is a significant decrease in the number of viral copies produced during infection (Fig.…”
Section: Inhibition Of Hcov-nl63 Replication In Vitromentioning
confidence: 99%
“…Increased attachment of bacteria to virus-infected cells and tissue has been observed for numerous combinations of respiratory pathogens, some of which will be discussed in more detail below (Avadhanula et al, 2006;Golda et al, 2011;Ha kansson et al, 1994;Hament et al, 2004;Jiang et al, 1999;Raza et al, 1993;Sanford & Ramsay, 1987;Wang et al, 2009). Generally, bacterial attachment can be enhanced by (1) increased expression of host receptors after viral infection or (2) by viral structures serving as coupling agents for bacteria to host tissues.…”
Section: Enhancement Of Bacterial Bindingmentioning
confidence: 99%